GAMBARAN KUALITAS UDARA RUMAH SAKIT TK III REKSODIWIRYO KOTA PADANG - Hidayanti, Rahmi; Zicof, Erick; Nur, Erdi; Gusti, Awalia (HUMAN CARE JOURNAL, 2024)
Air as an environmental component needs to be maintained and improved in quality so that it provides the supporting capacity for living creatures to live optimally. A hospital is a health service institution that provides comprehensive individual health, providing inpatient, outpatient and emergency services. Transmission of nosocomial infections in hospitals occurs through various means, one of which is air. Physical environmental conditions such as humidity, lighting and temperature influence the growth and development of disease-causing germs such as viruses and bacteria which can cause health problems for visitors, patients and health workers in hospitals. This research was descriptive in nature with laboratory examinations, carried out at TK III Reksodiwiryo Hospital, Padang City. The population in this study was the air of the inpatient room at TK III Reksodiwiryo Hospital, Padang City. The research sample was taken based on several researchers' considerations. The samples in this study were the children's inpatient room, the Bung Hatta inpatient room, the ICU room and the OK room. Physical air quality checks consist of temperature, humidity and lighting. The results of checking the temperature of the inpatient room when compared with PMK No. 2 of 2023 concerning Implementing Regulations of Government Regulation Number 66 of 2014 concerning Environmental Health exceed the standards that have been set. Advice that can be given to hospitals is to pay attention to factors that can influence air quality both physically and biologically so that air pollution in hospitals can be overcome